Forced expiratory volume in 1 second percentage improves the classification of severity among children with asthma. - Fuhlbrigge, Anne L; Weiss, Scott T; Kuntz, Karen M; Paltiel, A David (Pediatrics, 2006)
Spirometry is an important component of the National Asthma Education and Prevention Program guidelines for asthma, yet published data show variable associations between forced expiratory volume in 1 second percentage (FEV1%) predicted, symptoms and health care utilization. The objective of this analysis was to examine the association between FEV1% and future risk of exacerbations among a well-characterized population of children with asthma.
Keywords: Albuterol; Anti-Asthmatic Agents; Asthma; Bronchial Provocation Tests; Bronchodilator Agents; Budesonide; Child; Child, Preschool; Cohort Studies; Double-Blind Method; Emergency Service, Hospital; Ethnic Groups; Female; Follow-Up Studies; Forced Expiratory Volume; Hospitalization; Humans; Male; Methacholine Chloride; Models, Theoretical; Multicenter Studies as Topic; Nedocromil; Randomized Controlled Trials as Topic; Risk; Severity of Illness Index; Spirometry; Treatment Outcome